Possibilities of using the European bison (Bison bonasus) epididymal spermatozoa collected post-mortem for cryopreservation and artificial insemination: a pilot study - Dubiel Andrzej; Niżański Wojciech; Kozdrowski Roland; Olech Wanda (BMC, 2011)
Abstract Background European bison is the largest mammal in Europe with the population of approximately 4000 individuals. However, there is no report of post-mortem spermatozoa collection and cryopreservation from this species and the aim of this study was to test if the epididymal spermatozoa collected post-mortem from European bison are suitable for cryopreservation and artificial insemination (AI). Methods Epididymides were collected post-mortem from two European bison bulls at age of 8 (bull 1) and 11 year (bull 2). Epididymal sperm was harvested by making multiple incisions in caudae epididymidis, which were then rinsed with extender. The left epididymis of bull 1 was rinsed with BioXcell (IMV, France), whereas the right epididymis of bull 1 and the right and left epididymides of bull 2 were rinsed with the extender based on Tris, citric acid, glucose, egg yolk, glycerol, antibiotics and distilled water (extender II). The diluted semen was cooled to 5 degrees C, and frozen in liquid nitrogen vapour. Then, properties of the frozen/thawed semen were examined with the use of computer-assisted semen analysis system, and thirty cows and nine heifers of domestic cattle were artificially inseminated. Results Motility of fresh spermatozoa collected from the right epididymis of bull 1 was 70% (spermatozoa diluted with extender II), and from the left one was 60% (spermatozoa diluted with BioXcell), whereas motility of fresh spermatozoa collected from bull 2 was 90% (spermatozoa diluted with extender II). Spermatozoa motility just after thawing were 11 and 13% in bull 1, respectively for spermatozoa collected from the left and right epididymis and 48% in bull 2. As a result of AI of domestic cows and heifers with the frozen/thawed European bison spermatozoa, two pregnancies were obtained in heifers. One pregnancy finished with a premature labour after 253 days of pregnancy, and the second one after 264 days of pregnancy. Conclusions This is the first report showing pregnancy in the domestic cattle following AI with frozen-thawed European bison spermatozoa collected post-mortem. The protocol of spermatozoa collection, dilution, and cryopreservation presented in this paper may be useful for the creating genetic resource bank in the European bison.